First report of a Middle-Upper Permian magmatism in the SE Iberian Ranges: characterisation and comparison with coeval magmatisms in the western Tethys - Lago, M.; de la Horra, R.; Ubide, T.; Galé, C.; Galán-Abellán, B.; Barrenechea, J.F.; López-Gómez, J.; Benito, M.I.; Arche, A.; Alonso-Azcárate, J.; Luque, F.J.; Timmerman, M.J. (Journal of Iberian Geology, 2012)
A multiple basic to intermediate sill is reported for the first time in the south-eastern Iberian Ranges. It is composed of several tabular to irregular levels intercalated within the fluvial sediments of the Alcotas Formation (Middle-Upper Permian). The sill could represent the youngest Paleozoic subvolcanic intrusion in the Iberian Ranges. The igneous rocks are classified as basaltic andesites. They show a subophitic microstructure constituted by plagioclase (An62 – An6), augite (En48Wo44Fs7 –En46Wo39Fs15), pseudomorphosed olivine, minor amounts of oxides (magnetite and ilmenite) and accessory F-apatite. According to the mineralogy and whole-rock composition, their geochemical affinity is transitional from subalkaline to alkaline. Radiometric dating of the sill is not feasible due to its significant alteration. Field criteria, however, suggest an emplacement coeval to the deposition of the Alcotas Formation (Middle-Upper Permian). This hypothesis is supported by the transitional affinity of these rocks, similar to other Middle-Upper Permian magmatisms in the western Tethys, e.g., from the Pyrenees. Taking into account their isotopic signature (εSr: -6.8 to -9.2; εNd: +1.7 to +8.3), an enriched mantle source with the involvement of a HIMU component has been identified. This interpretation is supported by the trace element contents. Some of these HIMU characteristics have been recognised in the Middle-Upper Permian magmatisms of the Central Pyrenees (Anayet Basin) and the High Atlas (Argana Basin). However, none of these source features are shared with other Middle-Upper Permian magmatisms of the western Tethys (Catalonian Coastal Ranges, Corsica-Sardinia and southern France), nor with the Lower Permian magmatism of the Iberian Ranges. These differences support the presence of a heterogeneous mantle in the western Tethys during the Permian.